Balai, Pilipinas a Philippine indigenous culture-inspired hotel and resort - Pilar, Joshua D.
Balai Pilipinas: a Philippine indigenous culture-inspired hotel and resort is a 6-ha hotel and resort which is composed of: a three-wing hotel, a terraced resort area, and a group of private villas. The primary concept is the integration of varying characteristics may it be functional, cultural and/or physical from different indigenous dwelling to a single, unifying complex. The hotel has 250 bedrooms and can accommodate up to 700 people. It is composed of three buildings which are named as: Luzon, Visayas and Mindanao. They have similar facade design but each expresses their own distinct characteristics through interior and spatial features. There are 12 villas, which all can accommodate 3-5 people each. Each has their own private boat-shaped pool which is inspired by the culture of Badjao. Finally, the resort's site development plan is inspired by the Banaue Rice Terraces. The different facilities which can attract guests are: 5 swimming pools, zip line station, chairlift station, foot trail, camping area, pavilion, and a viewing deck.